Climate-Neutral Energy Production - Prospects in Hungary in 2024 - Gácsi, Dániel; T. Kiss, Judit (International Journal of Engineering and Management Sciences, 2024)
In order to protect our planet's climate, it is important to reduce humanity's carbon dioxide emissions significantly. The energy sector is one of the most polluting industries, but the rapid spread of renewable energy sources over the past 20 years can significantly contribute to the reduction of carbon dioxide emissions. The study examined which energy sources are used to produce electricity in Hungary, and how the proportion of renewable energy has developed in recent years compared to more polluting energy production methods. There is a strong negative exponential relationship between the share of renewable energy and the carbon dioxide emissions of the energy sector, based on which the carbon dioxide emissions of the energy sector can be significantly reduced by increasing the share of renewable energy. A forecast was made for the renewable share based on past data and the revised state of the National Energy and Climate Plan in 2023, and a linear forecast was made for the energy sector's emissions. There is a strong exponential relationship between the data series. Both models examined in the study had strong explanatory power, but neither model supports the possibility of climate-neutral energy production by 2030.